PSYCHOLOGICAL CONDITION CONSTRAINTS OF LEARNING PARTICIPANTS IN STUDYING ENGLISH (Study at Learning Group of Package “C” in Community Learning Center / Pusat Kegiatan Belajar Masyarakat (PKBM) Nugraha Mandiri Cimahi City – West Java Province) - Sudiyono Sudiyono (IKIP Siliwangi, 2020)
This study reviewed the condition of learning participants’ at the study group of package “C” equivalent to SMA / SMK in the Community Learning Center (PKBM) Nugraha Mandiri which is located at Jalan Sawah Lega number 70 A, Cipageran Village, North Cimahi District, Cimahi City - West Java Province. The condition of learning participants in this research were psychological constraints. Psychological constraints in this paper were limited only to : (a) interest in learning; (b) learning motivation; (c) intelligence; and (d) learning activities of the learning participants population. The writing of this study is entitled Psychological Condition Constraints of Learning Participants in Studying English (Study at Learning Group of Package “C” in Community Learning Center/PKBM Nugraha Mandiri Kota Cimahi. The sample taken for this study was all the learning participants totaling 32 people, so this study was also called population research. The study was conducted using observation techniques, document studies, and interviews. While the research approach is a qualitative descriptive approach, which is a study whose purpose is to describe how the activities and conditions of the object under study. The steps for collecting and processing data are as follows: (1) conducting a preliminary study; (2) conduct document studies, observations and interviews; (3) do data processing; data is processed by doing simple calculations such as finding the sum and average amount. The results of the research show that more than 50% of the learning participants face psychological factor constraints, and further this condition affects their learning behavior.